A Generational War Is Launched with The Birth of Ok Boomer in The Digital Age - Young Joon Lim; Jennifer Lemanski (The Journal of Society and Media, 2020)
This study examined recent virality of œOk Boomer in the United States. The term of Ok Boomer gained overnight momentum in the public sphere as the symbol of a generational war. While previous research has primarily examined racial and gender tensions, this study introduced a new phenomenon of the generational conflict between œOk Boomers and œBaby Boomers, in which social media originated the term of Ok Boomer and traditional media diffused it with framed meaning. Diffusion of Innovation theory was used to better understand the path of how œOk Boomer as a catchphrase, hashtag, noun cluster or trend resulted in attracting a massive amount of media and public attention. Relying on Node XL, Google Trends, and Nexus Nexis for data gathering and analyses, this study categorized four themes for a word, or an idea as an innovation to be publicly acknowledged: collaboration of social media and traditional media, public figures involvement for debate; confrontational social issues, and media-framed agenda. In sum, this study argues the term of Ok Boomer symbolizes the advent of a generational war in society in line with the long-standing race and gender wars in the media coverage.